2015
DOI: 10.1103/physreve.92.042142
|View full text |Cite
|
Sign up to set email alerts
|

Confinement effects upon the separation of structural transitions in linear systems with restricted bond fluctuation ranges

Abstract: By means of advanced parallel replica-exchange Monte Carlo methods we examine the influence of elasticity and confinement on the structural transitions of linear systems with restricted bonded interaction. For this purpose, we adopt a model for coarse-grained flexible polymers of finite length in the dilute regime. Hyperphase diagrams are constructed using energy-dependent canonical quantities to demonstrate the effects of the changes in the range of the confined interaction on the liquid and solid structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, already, the variation of the short-range attraction range [101,102,103] may alter the structural transition of a flexible polymer to directly fold into its frozen state or even foster new low-temperature states. Similarly, a modification of the bond-interaction range alters the second-order collapse transition into a first-order condensation transition of coupled monomers [104]. Extending the model by torsional angles and adjusting a proper combination of confined bending and torsional angles again leads to the stabilization of helical structures [105,106].…”
Section: Phase Behavior Of Isolated Semiflexible Polymersmentioning
confidence: 99%
“…Interestingly, already, the variation of the short-range attraction range [101,102,103] may alter the structural transition of a flexible polymer to directly fold into its frozen state or even foster new low-temperature states. Similarly, a modification of the bond-interaction range alters the second-order collapse transition into a first-order condensation transition of coupled monomers [104]. Extending the model by torsional angles and adjusting a proper combination of confined bending and torsional angles again leads to the stabilization of helical structures [105,106].…”
Section: Phase Behavior Of Isolated Semiflexible Polymersmentioning
confidence: 99%
“…It could be shown that the stability and existence of a globular or liquid phase in models of flexible polymers depends on the effective interaction range between nonbonded monomers [7][8][9][10]. A recent study of the influence of bond confinement upon structural phases and transition behavior of a flexible chain showed that the liquid phase also disappears with increasing bond fluctuation range and the gas-liquid and the liquid-solid transition lines merge [11]. Bending restraints in helical polymers can lead to the formation of stable helix bundles, resembling tertiary structures in biopolymers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most efficient simulation methods are the generalized-ensemble Monte Carlo algorithms, such as simulated tempering [4,5], replica-exchange parallel tempering [6][7][8][9], multiple Gaussian modified ensemble (MGME) [10], together with multicanonical [11][12][13][14][15][16] and Wang-Landau sampling [17][18][19]. These have been applied successfully in numerous studies of structural phases and transition properties [20][21][22][23][24][25][26][27][28][29][30][31], surface adsorption [32][33][34][35][36][37][38][39][40][41], and aggregation [42][43][44][45][46][47] of generic off-lattice homopolymers and heteropolymers. The folding properties of coarse-grained protein models have also been examined extensively [48][49]…”
Section: Introductionmentioning
confidence: 99%